Epidemiology and Factors Influencing Davis Cup Retirements Over the Past Twenty Years - Martí Casals; Jordi Cortés; Daniel Llenderrozos; Miguel Crespo; Timothy E. Hewett; Lorena Martin; Ernest Baiget (North American Sports Medicine Institute, 2024)
# Background The demands of professional tennis, including physical and psychological aspects, contribute to the frequency of retirements at elite levels of the sport. # Purpose The aim of this study was to explore the frequency of injuries and the factors that influence the retirements of professional tennis players competing in the Davis Cup over the last two decades. # Study Design Retrospective cohort study. # Methods The data set includes data from 6,060 men's singles matches that included 1,814,141 games from Davis Cup ties played between 2000 to 2019. Factors that might influence the retirements were studied by means of generalized linear models using Poisson distribution. Incidence rates by 1000 games and incidence rate ratios of retirements are provided as association measures. # Results The retirement incidence was 1.05 per 1000 games \[95% CI: 0.90, 1.21\]. The main risk factors associated with retirements were matches played on hard courts (IRR: 2.52 \[95% CI: 1.32, 4.83\]) and matches played in the final two matches of the tie and in a best-of-5-set format (IRR: 2.63 \[95% CI: 1.69, 4.09\] and IRR: 5.52 \[95% CI: 3.50, 8.69\], respectively). The most common injuries that led to retirements were those affecting the lower extremities, specifically involving muscular or tendinous tissues. # Conclusion This study provides valuable insights for coaches, players, support teams, and epidemiologists regarding retirements and their associated risk factors in Davis Cup tournaments. These findings may guide future research and inform strategies aimed at managing player health and performance in professional tennis. # Level of evidence Level 2b.